TRANSFORMING WIRELESS SECURITY: HARNESSING THE POTENTIAL OF ARTIFICIAL INTELLIGENCE IN RADIO FREQUENCY FINGERPRINTING - Bekhzod Sulaymonov (Journal Park Publishing, 2023)
This article discusses the integration of Artificial Intelligence (AI) with Radio Frequency (RF) fingerprinting, an essential technique for wireless security and device authentication. Traditional RF fingerprinting faces difficulties in signal complexity and device diversity, whereas AI’s capabilities in pattern recognition and data analysis offer a possible solution. This approach guarantees improved accuracy in identifying devices by making use of machine learning as well as neural networks. Therefore, this paper provides an extensive exploration of AI algorithms used in RF fingerprinting, highlights current advancements and explores practical applications thereby affirming the transformative potential of AI in this domain.
Keywords: frequency, fingerprinting, artificial intelligence, machine learning, wireless, security.